Method of using multiple perceptual channels to increase user absorption of an N-dimensional presentation environment - MAPLES; CREVE; PETERSON; CRAIG A (1999)
A multi-dimensional user oriented synthetic environment system allows application programs to be programmed and accessed with input/output device independent, generic functional commands which are a distillation of the actual functions performed by any application program. A shared memory structure allows the translation of device specific commands to device independent, generic functional commands. Complete flexibility of the mapping of synthetic environment data to the user is thereby allowed. Accordingly, synthetic environment data may be provided to the user on parallel user information processing channels allowing the subcognitive mind to act as a filter, eliminating irrelevant information and allowing the processing of increase amounts of data by the user. The user is further provided with a craft surrounding the user within the synthetic environment, which craft, imparts important visual referential an motion parallax cues, enabling the user to better appreciate distances and directions within the synthetic environment. Display of this craft in close proximity to the user's point of perspective may be accomplished without substantially degrading the image resolution of the displayed portions of the synthetic environment.